A Transcriptional Signature of IL-2 Expanded Natural Killer Cells Predicts More Favorable Prognosis in Bladder Cancer - Sun, Yuhan; Sedgwick, Alexander James; Khan, Md Abdullah-Al-Kamran; Palarasah, Yaseelan; Mangiola, Stefano; Barrow, Alexander David (Frontiers in Immunology, 2021)
Activation of natural killer (NK) cell function is regulated by cytokines, such as IL-2, and secreted factors upregulated in the tumor microenvironment, such as platelet-derived growth factor D (PDGF-DD). In order to elucidate a clinical role for these important regulators of NK cell function in anti-tumor immunity, we generated transcriptional signatures representing resting, IL-2 expanded, and PDGF-DD activated, NK cell phenotypes and established their abundance in The Cancer Genome Atlas bladder cancer (BLCA) dataset using CIBERSORT. The IL-2 expanded NK cell phenotype was the most abundant in low and high grades of BLCA tumors and was associated with improved prognosis. In contrast, PDGFD expression was associated with numerous cancer hallmark pathways in BLCA tumors compared to normal bladder tissue and a high tumor abundance of PDGFD transcripts and the PDGF-DD activated NK cell phenotype were associated with a poor BLCA prognosis. Finally, high tumor expression of transcripts encoding the activating NK cell receptors, KLRK1 and the CD160-TNFRSF14 receptor-ligand pair, were strongly correlated with the IL-2 expanded NK cell phenotype and improved BLCA prognosis. The transcriptional parameters we describe may be optimized to improve BLCA patient prognosis and risk stratification in the clinic and potentially provide gene targets of therapeutic significance for enhancing NK cell anti-tumor immunity in BLCA.